Analisis Akuntabilitas Pengelolaan Keuangan Bumdes - Safarudin, Agus (CV. Kalimasada Group, 2024)
This research aims to analyze and describe the accountability of BUMDes financial management in Sungai Jambat village, Sadu subdistrict, East Tanjung Jabung district. This type of research is qualitative research with descriptive data analysis methods where data collection techniques are carried out by means of observation, interviews and documentation. The informants in this research were the village head, BPD chairman, BUMDes coordinator, BUMDes director, secretary, treasurer, and the community. The results of the research show that the financial management of BUMDes Sungai Jambat begins with the planning stage, namely holding a deliberation, which is attended by the BPD chairman, village head, BUMDes administrators, and the RT head as the community representative, then the administration stage, reporting stage and accountability stage which includes all these stages. has been carried out very well and follows applicable laws. In this case, the financial management of BUMDes in Sungai Jambat Village has implemented the principle of accountability which is supported by the principle of transparency, which is proven by the BUMDes management completing monthly income and expenditure information boards, as well as annual financial reporting and accountability reports.